Sharing code: A group of people must find out a secret code by analyzing a table available to all. Each participant knows his line in the table and one word from the code. A participant is allowed to announce to all others only one of two messages — s/he knows the code or does not know it. The article describes an algorithm allowing the construction of the table, with the help of which, after a few exchanges of messages, all participants will recognize the code. - Коточигов, Александр Михайлович; Левицкий, Даниил Владимирович; Носова, Ольга Андреевна (Computer Tools in Education, 2017)
Saint-Petersburg Electrotechnical University, Saint Petersburg, Russia